FBXW7 promotes autophagy and inhibits proliferation of oral squamous cell carcinoma - Bo Qiu; Yang Sun; Wei Nie; Qi Yang; Xiangjun Guo (Immunity, Inflammation and Disease)
Abstract Background F‐box and WD repeat domain containing 7 (FBXW7) is a critical tumor suppressor. The expression of FBXW7 is decreased in oral squamous cell carcinoma (OSCC) tissues and shows diagnosis value. We aimed to investigate the influence of FBXW7 overexpression on OSCC cell proliferation and autophagy. Methods In Balb/c nude mice, CAL27 xenograft tumor model was established. Western blot was employed to evaluate protein level. Messenger RNA level was analyzed by quantitative reverse transcription‐polymerase chain reaction. Colony formation assay and MTT assay were employed to evaluate cell proliferation. Results FBXW7 expression was decreased in OSCC cell lines. FBXW7 inhibited cell proliferation of SCC9 and CAL27. FBXW7 increased Autophagy related 7 (Atg7), Beclin1 (BECN1), B‐cell lymphoma 2 (BCL2) ‐associated X (BAX), BCL2 antagonist killer (BAK), and microtubule‐associated protein 1 light chain 3 (LC3) levels and decreased MCL1 and BCL2 levels in CAL27 cells. FBXW7 decreased tumor volume and weight in CAL27 xenograft tumor model. FBXW7 increased BECN1, Atg7, and LC3 levels in CAL27 xenograft tumor model. Conclusion In conclusion, decreased expression of FBXW7 is confirmed in diverse OSCC cell lines. The enhanced FBXW7 expression inhibits cancer cell proliferation and promotes autophagy in both OSCC cells and xenograft tumor model.